Ołtarze okazjonalne wznoszone w czasie procesji Bożego Ciała w kolonialnym Cusco - Kubiak, Ewa (TECHNE. Seria Nowa, 2018)
During the colonial period, the celebration of secular and religious feasts became a crucial element of socio-religious life in Latin America. Such festivals were one of the tools that facilitated evangelisation. Additionally, it should be remembered that any religious holiday in colonial Peru and Mexico, especially in the areas dominated by the indigenous peoples, constituted a cultural blend of Catholic customs (brought from Europe by the Spanish) and the traditions of native Indian tribes. The feasts celebrated in the 17th and 18th centuries can be divided into one-time and cyclic. The former included beatifications and canonisations, enthronements, proclamations, and exequies, while the recurring celebrations were connected with the liturgical year and particular Marian and Christological devotions, or related to individual saints, thus having a rather local character. This paper focuses on the architecture of procession altars erected in Cusco for the celebrations of Corpus Christi in the colonial period, the first celebration of which, according to Inca Garcilaso de la Vega, took place in 1555. Its procession intended to celebrate the triumph of the new religion brought from Spain, while still observing local traditions. This festival was and still remains one of the most important events of the liturgical year. Another important event was the incorporation of Corpus Christi into the 1572 Ordinances of Viceroy Toledo for the City of Cuzco (Ordenanzas del virrey Toledo para la ciudad del Cuzco). The most significant source materials facilitating the research on Cusco’s ceremonial architecture include paintings of the time, and the preserved archival documentation and chronicles. Among the former, the most useful is the famous series of works portraying a Corpus Christi procession, which are believed to have been painted in the final quarter of the 17th century, at the request of Bishop Manuel de Mollinedo y Angulo. Even though some paintings only show procession figures carried on carts, others present sculptures of saints mounted on andas and carried by cargadores, with altars and triumphal arches in the background. The most important source documentation includes agreements concluded between benefactors and contractors stored in Archivo Reginal del Cusco. Other helpful materials are the church inventories preserved in the archbishop’s archives, church construction logbooks (libros de fabrica) and documents related to confraternities operating at various churches in Cusco, which can be accessed in Archivo Arzobispal del Cusco. Based on these materials, it was possible to conduct an analysis of the ceremonial architecture in Cusco, taking into account the following three aspects: the form and the building materials of the researched objects, and their iconography. The altars erected in Cusco for the purposes of Corpus Christi processions had a predetermined form. The vast majority were pyramidal compositions with lavish ornamentations, whose aim was not only to add splendour to religious celebrations, but also to manifest the wealth and religious piety of the originators, benefactors, and also the artists themselves. Most materials used to construct and decorate procession altars were already known in Europe, including miscellaneous types of fabrics, textiles and expensive silver and tortoiseshell, but occasionally also such typically Andean materials as maguey (ligneous parts of the agave used in sculpting figures) and feathers. The dominating iconographic motif presented in the altars is related to the establishment, worship and triumph of the Blessed Sacrament, with the major representations including the Eucharistic Adoration and the Last Supper, the Crucifixion, the Eucharist, the Defence of the Eucharist, scenes from the Transfiguration of Jesus, and images of the Christ Child. These and other altar representations are based on famous painting compositions popular among the representatives of the Cusco School.